Sir Henry Clinton papers - Clinton, Henry, Sir, 1738?-1795.
Chiefly volumes and pamphlets, with annotations by Clinton, relating to the controversy between Clinton and Charles Cornwallis, marquis Cornwallis.
British army officer.
Collection material in English.
Keywords: Cornwallis, Charles Cornwallis, -- Marquis, -- 1738-1805.